The wing in yeast heat shock transcription factor (HSF) DNA-binding domain is required for full activity - Cicero, Marco P. (Oxford University Press, 2001)
The yeast heat shock transcription factor (HSF) belongs to the winged helix family of proteins. HSF binds DNA as a trimer, and additional trimers can bind DNA co-operatively. Unlike other winged helix–turn–helix proteins, HSF’s wing does not appear to contact DNA, as based on a previously solved crystal structure. Instead, the structure implies that the wing is involved in protein–protein interactions, possibly within a trimer or between adjacent trimers. To understand the function of the wing in the HSF DNA-binding domain, a Saccharomyces cerevisiae strain was created that expresses a wingless HSF protein. This strain grows normally at 30°C, but shows a decrease in reporter gene expression during constitutive and heat-shocked conditions. Removal of the wing does not affect the stability or trimeric nature of a protein fragment containing the DNA-binding and trimerization domains. Removal of the wing does result in a decrease in DNA-binding affinity. This defect was mainly observed in the ability to form the first trimer-bound complex, as the formation of larger complexes is unaffected by the deletion. Our results suggest that the wing is not involved in the highly co-operative nature of HSF binding, but may be important in stabilizing the first trimer bound to DNA.